OPTIMIZATION OF PLAYGROUND FACILITIES FOR SOUTH OESAPA EARLY CHILDHOOD EDUCATION IN ORDER TO SUPPORT THE LEARNING PROCESS - Kristomus Boimau; Wenseslaus Bunganaen; Adi Y Tobe; Rima Nindia Selan (Jurnal Pengabdian Vokasi, 2025)
The purpose of this service activity is to optimize play facilities in order to support the learning process at PAUD Marturia Oesapa Selatan. Play facilities can help provide stimulation to help with physical and spiritual growth and development so that children have readiness to enter further education. The existence of good facilities and infrastructure can support the learning process to be more optimal which affects the quality of education. Data sources are obtained through observation, interview, and documentation methods. Interview informants include school principals, teachers of facilities and infrastructure, and subject teachers. The implementation method carried out by the implementation team in order to overcome partner problems is divided into 3 stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of the activity show that the playground facilities have been well managed and stakeholders are satisfied.